STAIR IN BALINESE TRADITIONAL HOUSE AN ERGONOMIC APPROACH - Gede Suyoga, I Putu (Jurnal Natah, 2012)
Stair in Balinese traditional house is a link between the open space (natah) and the building floor. Essentially, the rise and the tread of stair are defined strongly by the traditional norms and techniques. The stairs as product of traditional innovation is most likely the ergonomics aspect having been taken into account as an important aspect. Based on that reason, it is essential to conduct research in order to explore and investigate the ergonomics aspect of design stair on Balinese traditional house. The research shows that between the stair dimension and the anthropometrics of the house owner have closely relationship, and its design has required the safety and comfortable of the user.
Keywords: stair, dimension, traditional norm